Primera parte del Parnaso antartico, de obras amatorias : con las 23 epistolas de Ovidio, selin Ibin [i.e. i el Ibis], en tercetos - Ovid, 43 B.C.-17 A.D. or 18 A.D; Pérez Rincón, Cristóval; Pérez Angel, Luis; Soto, Pedro de, -1563; Oña, Pedro de, 1570?-1643?; Mexía, Diego, -approximately 1617 (Sevilla : A. Rodriguez Gamarra, 1608)
Bibliotèque Nationale de Paris has the only copy of the unpublished manuscript of the second part, entitled: Segunda parte del Parnaso antartico de divinos poemas. Cf. Palau y Dulcet Sonnets by Pedro de Oña, Pedro de Soto and Luis Pérez Angel on preliminary leaves [5]-[6]; sonnet by Cristóval Pérez Rincón on leaf 265 [i.e. 267] Vignette on t.p. with inscription: Si Marte llevo al ocaso las dos colunas, Apolo llevo al antartico polo a las musas i al Parnaso Leaves printed on both sides Palau y Dulcet (2. ed.) Mode of access: Internet.